2021
DOI: 10.1002/ijop.12818
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive emotion regulation strategies and psychological distress during lockdown due to COVID‐19

Abstract: Several governments have implemented strict measures to reduce the spread of COVID‐19, such as lockdown measures. However, these measures have brought negative consequences at an individual level by exacerbating the psychological distress caused by the pandemic. We evaluated the role of cognitive emotion regulation strategies (CERS) on the levels of anxiety and depression during the lockdown in a sample of 663 Spanish‐speaking adults, while controlling for variables related to social support, hobbies, seeking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
13
0
6
Order By: Relevance
“…In addition, the percentage of persons presenting low levels of stress was higher in our study (46.3%) that in Passavanti et al [ 9 ]. Rodas et al [ 24 ] administered the CES-D to a sample of 663 participants in Ecuador during the early stages of the pandemic (March to June) and, although prevalence scores for depression were not reported, the sample average was 19.6 (SD = 11.05), which is above the suggested cut-off score of 18 for the detection of depression. Furthermore, Tusev et al [ 22 ] and Caycho-Rodriguez et al [ 21 ] both found higher levels of significant depression (25% and 25.9% respectively) and anxiety (31.8% and 25.4% respectively) in large online samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the percentage of persons presenting low levels of stress was higher in our study (46.3%) that in Passavanti et al [ 9 ]. Rodas et al [ 24 ] administered the CES-D to a sample of 663 participants in Ecuador during the early stages of the pandemic (March to June) and, although prevalence scores for depression were not reported, the sample average was 19.6 (SD = 11.05), which is above the suggested cut-off score of 18 for the detection of depression. Furthermore, Tusev et al [ 22 ] and Caycho-Rodriguez et al [ 21 ] both found higher levels of significant depression (25% and 25.9% respectively) and anxiety (31.8% and 25.4% respectively) in large online samples.…”
Section: Discussionmentioning
confidence: 99%
“…Passavanti et al [ 23 ], in the above-mentioned seven multi-country comparison, found Ecuador had the highest levels of anxiety on the DASS-21, and high trauma scores in the IES-R were noted as well. Rodas et al [ 24 ] found high mean level of depression using the Center for Epidemiological Studies Depression Scale (CES-D), but no prevalence was reported.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, si la información emitida por las autoridades y sus actos se contradicen, como ha ocurrido con buena parte de los gobiernos latinoamericanos, entonces se crean situaciones disonantes que, en las condiciones de una pandemia, aumentan el enojo, la incredulidad, la tensión, el miedo, la angustia y los estados de depresión y desesperación en las personas, que además deben enfrentar efectos devastadores en sus economías, relaciones sociales y pérdidas que en muchos casos son irreparables. Lo anterior configura un reto para las personas en el afrontamiento emocional del COVID-19 (Dinić & Bodroža, 2021;Zajenkowski et al, 2020) y en la necesidad de establecer estrategias de afrontamiento cognitivo-emocionales (Rodas et al, 2021). En consecuencia, los estados emocionales y los esfuerzos por redu-cir la disonancia cognitiva en contextos de incertidumbre, sobrecarga y alta ambivalencia de información inciden a la forma de actuar políticamente ante los procesos electorales, pudiendo verse afectadas por el miedo, frustración o incertidumbre (Gil-Fortoul, 2021), además de afectaciones mentales más prevalentes como la ansiedad, depresión o estrés (Tusev et al, 2020).…”
Section: La Preocupación Asociada Al Covid-19 Y Sus Tipos De Influenc...unclassified
“…En este punto, resulta de interés explorar la relación entre la preocupación por el COVID-19 y sus posibles consecuencias movilizadoras o desincentivadoras en el comportamiento político online que desarrolla la población (Santana et al, 2020), a partir de la exposición a la información sobre la pandemia, que se ha caracterizado por tener un carácter marcadamente político (Burdman, 2020;Pérez-Curiel & Velasco Molpeceres, 2020;Rodríguez-Varela & Carbonetti-Parola, 2021). En este trabajo, se plantean dos rutas sobre cómo la preocupación por el COVID-19 tiene un efecto en la acción política: primero, como una vía desmovilizadora, en la cual la preocupación por las repercusiones del COVID-19 se asocia a un alto impacto emocional, impidiendo a las personas generar estrategias de regulación emocional, especialmente con respecto al manejo del miedo (Muñoz-Fernández et al, 2020;Rodas et al, 2021). A través de esta primera vía, la preocupación por el COVID-19 desencadena respuestas emocionales ancladas en el miedo, que desestimula el interés por participar de acciones políticas y prioriza la adopción de conductas de autoprotección como la utilización de mascarilla, lavado de manos, el consumo de información concerniente a la evolución de los contagios o las recomendaciones de bioseguridad por parte de las autoridades sanitarias, entre otras (Renström & Bäck, 2021) y lo político perderá interés (Salaverría et al, 2020).…”
Section: La Preocupación Asociada Al Covid-19 Y Sus Tipos De Influenc...unclassified
“…In this context, the pandemic has had significant effects on the short-term and medium-term mental health of people around the world ( Cullen et al, 2020 ; Lieven, 2021 ; Magano et al, 2021 ) and in Ecuador in particular ( Zumba-Tello & Moreta-Herrera, 2022 ). The psychological distress caused by the pandemic is exacerbated for individuals who have difficulties with cognitive emotion regulation strategies and with coping and conflict-resolution mechanisms ( Rodas et al, 2021 ). This results in overall symptomatology such as excessive stress, fear, anxiety, and depression, amongst others ( Chen et al, 2021 ; Moreta-Herrera et al, 2021 ; Vinaccia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%